Virtual Computer Laboratory Learning System Integrated With Social Media And Video Conference - Agus Hermanto; Dimas Dwi Ivandri (Publikasi Indonesia, 2024)
The advancement of information and communication technology has driven innovation in various aspects of education, including computer laboratory learning. Traditional computer laboratories often face challenges in terms of time, cost, and accessibility. To address these challenges, this study developed a virtual computer laboratory learning system integrated with social media and video conferencing. This system is designed to provide flexible access, allowing students to learn and practice anytime and anywhere. The integration of social media aims to enhance interaction and collaboration between students and instructors, while video conferencing enables real-time learning sessions with direct interaction. The research methods used include system design, software development, and system testing. The results showed that the virtual computer laboratory learning system integrated with social media and video conferencing can facilitate learning and is expected to be an innovative solution in information technology education.